Annotation of the Extracellular Enveloped Form of Monkeypox Virus for the Design, Screening, Validation, and Simulation of a Chimeric Vaccine Construct - Mohammad Asrar Izhari; Essa Ajmi Alodeani; Siraj B. Alharthi; Ahmad H. A. Almontasheri; Foton E. Alotaibi; Rakan E. Alotaibi; Wael A. Alghamdi; Osama Abdulaziz; Fahad Alghamdi; Ali Alisaac; Mansoor Alsahag; Ahmed R. A. Gosady (Biology)
Recent outbreaks caused by hMPXV, especially hMPXV lineages/sub-lineages, represent public health threats necessitating stringent prophylactic measures to ameliorate their colossal impact. The current study annotated the EEV form of hMPXV’s target proteins to formulate a reverse vaccinology-dependent hMPXV multiepitope vaccine. Epitope determination, followed by vaccine formulation, was undertaken. The promising formulation was validated for its potential to trigger immune responses immunoinformatically. The MPXV-1-Beta formulation was characterised as a promising candidate based on antigenicity score, physicochemical properties, solubility score, ProSA Z-score, and Ramachandran plot. Docking, normal mode analysis, and molecular dynamic simulation of MPXV-1-Beta with TLRs and MHCs authenticated rigid docking and its efficacy in enhancing immune receptor activation under physiological conditions. MPXV-1-Beta was discerned to trigger a sustained immune response (IR) with a broader average population coverage of 97.526, SD = 12.44. The proposed MPXV-1-Beta candidate showed significant potential. The findings of this study provide a preliminary framework for developing an efficacious hMPXV vaccine; however, extensive in vitro, in vivo, and clinical evaluations are required to substantiate the computational insights.